Identifying and analysing game styles and factors influencing a team´s strategy in field hockey - Lord, F.; Pyne, D. B.; Wevaert, M.; Mara, J. K. (Journal of Sports Sciences, 2022)
Characterising a team`s game style is a performance analysis approach that captures game events, and groups them into profiles using clustering techniques to identify the consistent (and winning) strategies a team implements. The aim of this study was to identify the game styles of international hockey teams. Video footage from the 2019 Pro League tournament (n = 74 female and n = 57 male matches) were analysed retrospectively using a notational analysis system in SportsCode™. Variables were arranged into six game style categories (established attack game actions, counter attack game actions, established attack success, counter attack success, set pieces, tempo) and two game style types identified per category using a k-means clustering algorithm. Decision trees were used to identify the influence of extrinsic and intrinsic match factors on the probability of a team playing a particular game style. Opposition and other reference team game style categories were shown to be more important in predicting a game style category than contextual factors. Examination of team profiles highlights how different strategies are successful for different teams such as high-intensity attack or absorbing pressure and counter attacking. This performance analysis process provides practical insights into the holistic performance of international hockey teams.